2003
DOI: 10.3317/jraas.2003.024
|View full text |Cite
|
Sign up to set email alerts
|

Toward a broader understanding of aldosterone in congestive heart failure

Abstract: Discovered some 50 years ago, aldosterone (ALDO) has come to be recognised as a mineralocorticoid hormone with well-known endocrine properties in epithelial cells that contribute to the pathophysiology of congestive heart failure. This includes Na + in such non-epithelial cells as peripheral blood mononuclear cells; its influence on endothelial cell function; and its central actions that involve regulation of cerebrospinal fluid composition produced by epithelial cells of the choroid plexus, activity of the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 125 publications
1
14
0
Order By: Relevance
“…a subsequent study showed that the combination of VPB plus couplets is an independent indicator of the total mortality rate after acute Mi (27). However, the mechanisms of this effect are unclear; several mechanisms may account for the reduction in mortality caused by spironolactone, such as attenuated sym pathetic tone (28,29) and improved parasympathetic activity (30,31), or direct inhibition of the Mi-induced increase in T-type calcium current (32,33). in this study, we found a correlation between improvements in the survival rate ( Fig.…”
Section: Discussionsupporting
confidence: 59%
“…a subsequent study showed that the combination of VPB plus couplets is an independent indicator of the total mortality rate after acute Mi (27). However, the mechanisms of this effect are unclear; several mechanisms may account for the reduction in mortality caused by spironolactone, such as attenuated sym pathetic tone (28,29) and improved parasympathetic activity (30,31), or direct inhibition of the Mi-induced increase in T-type calcium current (32,33). in this study, we found a correlation between improvements in the survival rate ( Fig.…”
Section: Discussionsupporting
confidence: 59%
“…The effects of AT 1 receptor activation may involve local production of superoxide [45]. Aldosterone, acting via mineralocorticoid receptors in the PVN, may also increase sympathetic activity [78]. Thus, the PVN has a pivotal role in the feedforward relationship between the renin-angiotensin-aldosterone axis and the sympathetic output controlling renin release, blood flow, and tubular Na + reabsorption by the kidney [35].…”
Section: ■ Congestive Heart Failurementioning
confidence: 99%
“…The role of the RAAS as a cause of fluid retention, endothelial and baroreceptor dysfunction, and vascular and myocardial remodeling in patients with chronic heart failure is well accepted. [1][2][3][4][5][6] The RAAS can also be activated pharmacologically by drugs often used to treat heart failure. These drugs include vasodilators such as amlodipine 7 and hydralazine 8 and diuretics such as furosemide.…”
mentioning
confidence: 99%